Comparison of maximal acid output and gastrin response to meals in Chinese and Scottish normal and duodenal ulcer subjects. Issue 4 (April 1980) - Lam, S K; Hasan, M; Sircus, W; Wong, J; Ong, G B; Prescott, R J
Abstract : Maximal acid output (MAO) after pentagastrin stimulation and gastrin response to a standard meal was studied in 100 control and 200 duodenal ulcer subjects from each of two ethnic groups, Scots and Chinese. The acid output was significantly higher in the Scots than in the Chinese for both controls and duodenal ulcer patients. Despite correction for differences in body stature by expressing MAO as a function of the body weight, these differences persisted. In 45 pairs of closely matched patients with duodenal ulcer, the differences between the two ethnic groups remained significant, irrespective of whether MAO was expressed in absolute or weight corrected values. This indicates that differences in age, sex, family history, or duration of illness did not account for differences in acid output. In 20 pairs of normal control and 45 pairs of duodenal ulcer patients the fasting and post-prandial serum gastrin levels did not differ, significantly between the two ethnic groups. The proportion of acid normosecretors was significantly higher in the Chinese duodenal ulcer patients than in the Scottish. The reason for these differences in the gastric acid output between the two ethnic groups is not known and needs to be studied further.